Dial M for mentor : reflections on mentoring in film, television, and literature - Gravells, Jonathan; Wallace, Sue (Emerald Publishing Limited : Information Age Publishing, 2011)
This book takes stories of learning relationships from popular films, television programmes and literature, and uses them as a catalyst for beginners and experts alike to reflect critically on their own mentoring and coaching practice. How realistic are our expectations of personal change, and to what extent is the flourishing self-help market responsible for this? What, if any, are the moral responsibilities of executive mentors and coaches, when it comes to global corporate wrongdoing? What should constitute 'truth' and 'knowledge' in a world in which ambiguity and doubt can appear more effective weapons of survival? What can Pinocchio, The Matrix, Star Wars or The Sopranos tell us about any of this?Storytelling and metaphor have become of increasing interest in research into leadership and learning. Here is a book which takes the idea of storytelling as a powerful aid to learning and change, and uses it to help practitioners and educators challenge their ideas on mentoring in an entertaining way, by asking themselves some of the difficult questions that these popular stories raise.